Climate Change, Moose and Humans in Northern Sweden 4000 cal. yr BP - Larsson, Thomas B.; Rosqvist, Gunhild; Ericsson, Göran; Heinerud, Jans (Journal of Northern Studies, 2012)
Major cultural and environmental changes took place in the interior of Northern Sweden, beginning about c. 4200 cal. yr BP (or 2200 cal. BC). We present a causal, plausible, relationship linking climate change, a key resource and human culture. Moose (Alces alces) disappeared relatively fast from the human culture evidenced by a rapid decrease in usage and symbolism. Given the climatic data reconstructed at hand, a drastic change towards colder and wetter conditions seems to have happened 4200–3600 BP, which affected moose population numbers and composition significantly. After analyzing multiple data sources we suggest that moose had become very rare due to climate change and that many of the northern Fennoscandian hunting cultures had no choice but to change their subsistence pattern and, perhaps, change their general way of life, as a response to the altered situation. Linking the past to the present we speculate whether climate change as the primary driver, together with human harvest as the secondary, can result in fast extinction of a key species.